TINJAUAN HUKUM KESEHATAN PEMASANGAN VENEER DI INDONESIA - Sumartini Dewi; Markus Suryoutomo (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2022)
Aesthetic dental care can be done in various ways, nowadays the most popular dental treatment is by applying veneers to the teeth. Even so, many people still do not understand that veneer treatment is the authority of dentists. This study aims to determine the regulation of veneer installation in positive law in Indonesia and the application of the law to violations of authority in veneer installation in Indonesia. The result of the research is that although it does not specifically regulate the veneer method, based on the Dentist Competency Standards, Law Number 29 of 2004 concerning Medical Practice has become a positive legal arrangement inIndonesia which becomes the legal umbrella for all forms of general medical practice and dentistry. The application of the law against violations of authority in veneer installation should be able to include elements of a more complex crime in several positive legal regulations in Indonesia. This is intended so that the public can learn about the powers of medical treatment that can only be carried out by medical personnel or doctors or dentists.